The sacrifice - Lewis, Beverly, 1949- (Lewis, Beverly, 1949- Abram's daughters, 2004)
Having already suffered unthinkable betrayals, Leah Eversol has accepted her life as "Abram's daughter," fitting willingly and comfortably into the family and work. But an unexpected family announcement brings unimaginable joy-- as well as incredible sorrow. Leah is once again caught between the yearnings of her heart and responsibility for her family.